1976
DOI: 10.3171/jns.1976.44.2.0191
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in regional CBF, intraventricular pressure, CSF pH and lactate levels during the acute phase of head injury

Abstract: The authors measured regional cerebral 133xenon (133Xe) blood flow (rCBF), intraventricular pressure (IVP), cerebrospinal fluid (CSF) pH and lactate, systemic arterial blood pressure (SAP), and arterial blood gases during the acute phase in 23 comatose patients with severe head injuries. The IVP was kept below 45 mm Hg. The rCBF was measured repeatedly, and the response to induced hypertension and hyperventilation was tested. Most patients had reduced rCBF. No correlation was found between average CBF and clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
5

Year Published

1977
1977
2000
2000

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(41 citation statements)
references
References 27 publications
4
32
0
5
Order By: Relevance
“…These elevated cerebral levels of lactate may contribute to brain acidosis after' trauma, which has been implicated by several authors as a causative factor in injury to the central nervous system [20,26,28,32,35,38]. Additionally, a correlation of CSF lactate levels to posttraumatic cerebral hyperaemia has been shown [3,12]. For others, however, brain acidosis is only an epiphenomenon associated with tissue injury [1,23,40].…”
Section: Discussionmentioning
confidence: 99%
“…These elevated cerebral levels of lactate may contribute to brain acidosis after' trauma, which has been implicated by several authors as a causative factor in injury to the central nervous system [20,26,28,32,35,38]. Additionally, a correlation of CSF lactate levels to posttraumatic cerebral hyperaemia has been shown [3,12]. For others, however, brain acidosis is only an epiphenomenon associated with tissue injury [1,23,40].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have suggested that to induce the physiological vasoconstrictory cascade, MABP should be increased above supranormallevels by inotropic support or by vasoactive drugs [9]. However, for many, autoregulation is a very sensitive property of the cerebrovascular bed that is impaired or abolished in many patients after severe head injury [5].…”
Section: Introductionmentioning
confidence: 99%
“…Blood flow during reperfusion greatly exceeds tissue demands for ox ygen (Gourley and Heistad, 1984), and in the brain this may lead to hemorrhage or swelling, thereby exacerbating the ischemic insult (Reigel et aI., 1987;Batjer et aI., 1989;Powers and Smith, 1990). Hyper emia may also exacerbate cerebral edema accom panying acute head injury (Enevoldsen et al, 1976).…”
mentioning
confidence: 99%